Shear Wave Elastography for Assessment of Changes in Abdominal Soft Tissues after Lipoabdominoplasty - Zhou, Renpeng; Ding, Angang; Lyu, Dongze; Wang, Chen; Wang, Danru (Aesthetic plastic surgery, 2024)
Background The changes in the elasticity of the abdominal skin, subcutaneous tissues and muscles after lipoabdominoplasty are still unknown. The aim of this study was to provide an objective assessment of tissue elasticity after lipoabdominoplasty using ultrasound elastography. Methods A total of 21 female patients (31–41 years old) who underwent lipoabdominoplasty from Oct 2019 to Mar 2022 were included in this retrospective study. The elastography values of the skin, subcutaneous tissues and abdominal muscles were obtained with the ultrasound shear wave elasticity imaging system pre-operation (Pre) and 6 months post-operation (Post) at four different points. Results Twenty-one female patients were included. The elasticity of the abdominal skin, subcutaneous tissues, rectus abdominis and external oblique abdominis significantly increased at 6 months post-operation. The improvements in abdominal soft tissue elasticity were not uniform across the examined points. Conclusions Significant changes in the elasticity of the abdominal skin, subcutaneous tissues and muscles were observed after lipoabdominoplasty. Ultrasound elastographic assessment was objective and feasible for evaluating the effect of lipoabdominoplasty on abdominal soft tissue. Level of Evidence III This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .